“The adventures of Conch and Coral” – The benefits of an universal prevention board game for children aged between 6-10 - Alexandre, Joana Dias (2021)
Sexual abuse is a high prevalence problematic that has a very significative and negative impact in a child or young person’s life, its family and the community. Disseminating the usage of universal prevention programs is fundamental. The aim of this study is to analyze whether the game “Vamos prevenir! As aventuras do Búzio e da Coral” (Agulhas et al., 2016), designed to be played by children between 6 and 10 years old, promotes the acquisition of knowledge to deal with eventual sexual abuse situations. We developed a quantitative study (with pre and post test), with a sample of 101 children from that age group, male and female, which had played the game. The results show that children evaluated the game in a very positive way; statistically significant differences in the number of incorrect and uncertain answers were found from the pre to the post test. Although modest, these results show the importance of increasing children’s understanding about sexual abuse enhancing protection factors.